Die Opiinae der äthiopischen Region (Hymenoptera: Braconidae). - Fischer, Maximilian (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There is attempted a taxonomic study of the aethiopic Opiinae. 5 of the 13 known genera of this subfamily have representatives in the aethiopic region (Opius Wesm., Gnaptodon Hal., Ademon Hal., Austroopius Szepl., and Thoracoplites Fischer). This publication deals with 100 species, 96 of them belonging to Opius Wesm., while each of the other 4 genera is represented by only 1 species. There are given keys for the identification of subgenera, sections, groups, and species. Detailed redescriptions of the already described species are given, as far as not yet done by the author in his earlier publications, with notes on lacalities and distribution. 27 species are described as new. Nomenclatural Acts angolanus Fischer, 1963 (Ademon), spec. n. unifossa Fischer, 1963 (Gnaptodon), spec. n. advenator Fischer, 1963 (Opius), spec. n. ankaratrensis Fischer, 1963 (Opius), spec. n. atomarius Fischer, 1963 (Opius), spec. n. atomosus Fischer, 1963 (Opius), spec. n. bekilyensis Fischer, 1963 (Opius), spec. n. carinatoides Fischer, 1963 (Opius), spec. n. circur Fischer, 1963 (Opius), spec. n. dembelanus Fischer, 1963 (Opius), spec. n. euaffinis Fischer, 1963 (Opius), spec. n. malkini Fischer, 1963 (Opius), spec. n. manifestarius Fischer, 1963 (Opius), spec. n. maraquoanus Fischer, 1963 (Opius), spec. n. martiarushensis Fischer, 1963 (Opius), spec. n. minusculus Fischer, 1963 (Opius), spec. n. mujenjanicus Fischer, 1963 (Opius), spec. n. praesentarius Fischer, 1963 (Opius), spec. n. rufimarginatus Fischer, 1963 (Opius), spec. n. sequentator Fischer, 1963 (Opius), spec. n. seyrigi Fischer, 1963 (Opius), spec. n. simplificatus Fischer, 1963 (Opius), spec. n. ugandanus Fischer, 1963 (Opius), spec. n.